Antigen receptor gene rearrangements reflect on the heterogeneity of adult Acute Lymphoblastic Leukaemia (ALL) with implications of cell-origin of ALL subgroups - a UKALLXII study. - Rai, L; Casanova, A; Moorman, A; Richards, S; Buck, G; Goldstone, A; Fielding, A; Foroni, L (2010)
Cytogenetic and molecular investigations of Acute Lymphoblastic Leukaemia (ALL) have identified the existence of distinct clinical subgroups. Molecular monitoring of clonal Immunoglobulin and T cell receptor (IG/TR) gene rearrangements has become an important tool in stratification of therapy of ALL. In order to determine whether certain features of the patient-specific rearrangements could hold further prognostic clues or provide information on the cell of origin of ALL, a comprehensive analysis of structural and biological features (V gene usage, coding frame and mutational status and complementarity-determining region -III length) of 473 IG/TR rearrangements identified in 229 adults with ALL was carried out. Distinct variable-gene usage profiles were identified between ALL subgroups, particularly for patients positive for BCR-ABL1 compared to MLL-AFF1 positive leukaemias; suggesting that the former is derived from a more mature B progenitor. Interestingly, occurrence of TRGV1-TRGV8 was prognostic for better event-free survival (31% at 4 years with vs. 0% at 4 years without, P = 0.05). The heterogeneity in clinical outcome is suggested by the basic molecular processes of antigen receptor gene rearrangements as shown in this work.